(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
The tourism industry is a major contributor to the global economy, fostering growth and creating job opportunities worldwide. However, it has yet to fully tap into the potential of a significant and often overlooked segment of the population: people with disabilities (PWDs). These individuals face various barriers to employment within the tourism sector, which limits the industry’s access to a diverse and talented workforce. PWDs can bring fresh perspectives, creativity, and a unique understanding of accessibility needs to a wide range of tourism roles. This research explores the impact of workplace features on job satisfaction, career growth, and the sense of inclusion for PWDs in the tourism industry. Researchers used a survey format to collect data from PWDs employed at tourist attractions across Metro Manila. Targeted questions were designed to guide the survey, and a sample of 20 PWD workers was selected using stratified sampling. This approach ensured the sample represented the diversity of the PWD population within the tourism industry, considering different disability types and job roles. An online survey tool was used for data collection, and the responses were analyzed using percentages and weighted means to assess the factors affecting PWDs’ work experiences. The survey results revealed that the majority of respondents felt several factors influenced their work experiences within the tourism industry. These factors included the physical accessibility of the workplace, support for mental and emotional well-being, government disability rights regulations, and opportunities to effectively use their skills and knowledge. The research also identified positive aspects for PWDs in Metro Manila’s tourist attractions, such as a sense of inclusion in some workplaces, recognition of their strengths by supportive colleagues and managers, and the presence of legal protections for their rights. s. The study also highlighted areas needing improvement to better support people with disabilities (PWDs) in the workplace, such as enhancing accessibility, managing stress, and addressing biases. These challenges affect PWDs in various ways, underscoring the importance of creating inclusive environments. By focusing on inclusivity, employee well-being, and providing growth opportunities, workplaces can tap into the unique talents and perspectives of PWDs. Tourism businesses that fail to make everyone feel welcome risk missing out on a valuable workforce and customer base. Many individuals with disabilities are eager to engage with the tourism industry and bring significant contributions to its growth